The Effect Of Using Modern Immersive Marketing Techniques On The Buying Decision Process - جديد , رشا (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research aims to study the effect of using immersive marketing techniques on the purchasing decision-making process, through its five stages, which include: the problem awareness stage, information gathering, alternatives evaluation, purchasing decision making, post-purchase behavior. The study adopted the descriptive and analytical approach to characterize the study variables, and the study also adopted the statistical method in processing the primary data that was collected using the questionnaire that was distributed intentionally sample of clients who meet the study requirement using modern marketing applications. Individuals using these applications. The researcher reached several results, the most important of which are: There is a good effect of using immersive marketing techniques on all stages of the purchase decision-making process. However, the level of confidence of the respondents in acquiring products through these applications is average, and appropriate payment methods are not available for the acquisition of these products due to the lack of electronic payment facilities. For Syrian customers, the equipment supporting Syrian marketing techniques is not well available.